(untitled) (Revista de Ensino em Artes, Moda e Design, 2025)
To overcome the functionalist and Eurocentric approach to Graphic Design teaching, undergraduate Design courses at the Federal University of Sergipe began including content on local printed matter. The focus, described in this text, was to provide History of Design students with practical experience through the study of graphic memory, emphasizing local sociocultural and political contexts in teaching. To inform this account of the classroom experience, the following were conducted: a theoretical review of the concept of graphic memory combined with a conception of Design teaching in Brazil; and an analysis of teaching experiences that emphasize local visual and cultural repertoires as a basis for practical projects, based on the results of local studies conducted by the Design, Culture, and Society Research Group (CNPq/UFS). The development of pedagogical strategies that connect local graphic memory and design practice through activities that primarily used 20th-century Sergipe printed matter is highlighted. As a result, it was understood that the active and critical integration of graphic memory into Design disciplines in Sergipe contributes to the development of professionals who are attentive to local cultural diversity. The aim is to contribute to the strengthening of teaching methodologies that not only value technique but also recognize graphic memory as an essential training tool, enabling the development of a critical and multifaceted perspective on local cultural artifacts, popular writing, historical archives, and peripheral aesthetics as sources of learning and resistance in the teaching of Design history in Brazil.